Annotations on the beginnings of conceptualism in latin america (2003)
From the very beginning. conceptual movements in Latin America offered particularities different from those that were occurring in Europe and the us because they were oriented toward the relationship between art and political and social context. The inquiries in general were conducted in a different direction to that of the tautological problem that worried so much British and American artists and that attributed art with a role that went much further than the research into its internal conditions. In the 1960´s many artists took over ideas from the notions of antiart and tried not only to transmit a message but also to modify their relationship with the public and delve into the possibility of having an artistic experience that also proved a useful tool for social change. The diverse propositions made by artists from the cities of Buenos Aires. Rosario and Sao Paulo were clear examples of such views. The texts written by the protagonists are inescapable sources that allow us to learn about the theoretical basis of their propositions.